Coherent polarization locking of thermal sensitive Ho:YAG laser - Chua, Chern Fei. (2013)
We had demonstrated the advantage of using Coherent Polarization Locking on thermal-sensitive Ho:YAG laser cavity. We overcome several thermal issues related to Ho:YAG laser by distributing the gain over a large volume. We passively coherent locked two orthogonal polarized lasers, achieving 9.6W of output power with near perfect (> 99%) combining efficiency. The resultant laser produced near diffraction-limited beam quality of M2 ~1.1 and excellent power stability. As compared to conventional laser cavity, we had shown the increased in single-pass absorption, suppression of output power saturation and improvement in beam quality using Coherent Polarization Locking.